ANALISIS PENGENDALIAN KUALITAS PROSES PHOSPHATING PADA PT CITRA TUBINDO TBK - Bagas Micola; Arsyad Sumantika (LPPM Universitas Putera Batam, 2026)
This study discusses quality control analysis in the phosphating process at PT Citra Tubindo Tbk, a manufacturer of Oil Country Tubular Goods (OCTG). The problem identified was the high rate of non-homogeneous defects in the phosphating process, reaching an average of 4.16% from January to August 2025, which exceeded the company's maximum standard of 2%. This research aims to identify the optimal process parameters to minimize defects and improve process stability using the Taguchi Method. The experimental design used an L9 (3^3) Orthogonal Array involving three control factors: solution pH, immersion time, and temperature. Based on the analysis of the Signal-to-Noise (S/N) Ratio and mean response, it was found that the optimal combination of parameters to minimize defects is a solution pH of 38, an immersion time of 10 minutes, and a temperature of 70°C. The implementation of this optimal level combination is expected to reduce process variability and significantly decrease the defect rate, thereby meeting the company's quality standards.